2022
DOI: 10.1111/cgf.14458
|View full text |Cite
|
Sign up to set email alerts
|

ZoomShop: Depth‐Aware Editing of Photographic Composition

Abstract: Figure 1: Using ZoomShop to edit a photograph [Tha16]. (a) An image of mountains (background) framed by trees (foreground). The user's goal is to make the boat bigger while keeping the framing of foreground trees. (b) Zooming in and cropping scales up the boat, but cuts out most of the trees and shore. (c) Left: With ZoomShop users can select depth ranges (yellow and green) and independently adjust each region while maintaining scene structure. Disoccluded and stretched pixels are shown in cyan. Right: Cyan pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Working from a single viewpoint limits the options for capturing these phenomena, and necessarily means that they are curvilinear perspectives. Later, I will discuss multiperspective techniques that offer more options for adjusting relative object scale (Badki et al, 2017;Liu et al, 2022).…”
Section: Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Working from a single viewpoint limits the options for capturing these phenomena, and necessarily means that they are curvilinear perspectives. Later, I will discuss multiperspective techniques that offer more options for adjusting relative object scale (Badki et al, 2017;Liu et al, 2022).…”
Section: Contentmentioning
confidence: 99%
“…One use is to make distant objects larger, in order to create "natural perspective" imagery, as discussed earlier. Computational Zoom requires a collection of photographs to be taken at the same time; our ZoomShop method (Liu et al, 2022) works from a single photograph and generalizes Computational Zoom to allow for smoother transitions between regions (and, thus, amounts to "infinite multiperspective" in some cases). Multiperspective projections in computer graphics can simulate other nonrealistic artistic techniques, such as de Chirico paintings (Agrawala et al, 2000), Hockney's joiners (Zelnik-Manor and Perona, 2007), cubism (Collomosse and Hall, 2003), and Disney multiperspective background panoramas (Wood et al, 1997).…”
Section: Computational Multiperspective Collagementioning
confidence: 99%
“…This technique was later developed into a plugin for Maya [31]. More recently, Liu et al [32] have shown a depth-based editing tool for layering, resizing and recompositing photographs to overcome some of the restrictions of linear perspective-based projections and produce images that match visual space more effectively.…”
Section: Alternative Nonlinear Approachesmentioning
confidence: 99%